Varieties of marxist humanism : philosophical revision in postwar Eastern Europe - Satterwhite, James H. (Series in Russian and East European studies ;, 1992)
Flourishing in eastern Europe in the 1950s and 1960s, Marxist humanism helped to delegitimize the communist regimes, and it provided an intellectual basis for the successful assault on European communism in the 1980s. In this first comparative study of the movement, James Satterwhite focuses on Poland, Czechoslovakia, Hungary, and Yugoslavia, the four countries where the critical use of Marxist thought as the basis for rejecting the official ideology was fully developed. He draws upon research in the original languages for the most part, as well as on interviews and discussions with the critical thinkers themselves. Included are the views of Leszek Kolakowski from Poland, Karel Kosik from Czechoslovakia, and Svetozar Stojanovic from Yugoslavia. Marxist humanism developed as a response to Stalinism from within Marxism. In their search for a human alternative to the dehumanizing experience of Stalinism, certain critical thinkers - philosophers and sociologists - began to reread and reevaluate the Marxist texts. They developed a philosophical critique and refutation of the official ideology that led inexorably to a critique of the social, political, and cultural dimensions of the Stalinist system. Satterwhite traces the development of Marxist humanism in eastern Europe through a presentation of the key concepts as they were formulated by the various thinkers at different stages in their own intellectual growth. While he brings out the distinct features of each group studied, he finds a remarkable similarity in the end product. The fundamental unity underlying their efforts was not accidental; it derived from their common purpose and shared humanist perspective. Notes and a comprehensive bibliography provide a useful guide to writings by and about these key figures in the post-World War II period, whose thinking has had such a profound influence on our own times.